Monoacylglycerol lipase regulates cannabinoid receptor 2-dependent macrophage activation and cancer progression - Wei Xiang (Nature Portfolio, 2018)
Tumour associated macrophages (TAMs) have an altered lipid metabolism. Here the authors show that downregulation of monoacylglycerols lipase MGLL in TAMs induces lipid accumulation and tumor progression by polarizing TAMs toward tumor-promoting through activation of cannabinoid receptor CB2.